Vocabulary Learning Strategies Employed by Gamers In The “Simulation Video Game” - Moh. Hasbullah Isnaini; Resda Cintami Laksana (Universitas PGRI Madiun, 2018)
This study aims at investigating the phenomena of vocabulary strategies used by gamers of the Harvest Moon game. A survey study was conducted to see the most and the least frequent strategies used by the gamers while playing the game. To gain the data, the researcher distributed a questionnare which is adapted from the Schmitt’s taxonomy of VLS namely determination, social (discovery), social (consolidation), cognitive, memory, and metacognitive strategies. The result of the present study shows that the most frequent strategy used is cognitive strategy, the mean is 2.28 which indicates that most of the gamers use this strategy to improve their vocabulary learning. Meanwhile, the least strategy used is the social startegy since the mean score is 1.07 which suggests that the gamers do not really seek help from friends when they have problems with vocabulary. Taking the result of the study into the learning of vocabulary, it is suggested that teachers provide language learners with the cognitive strategy to accomodate their vocabulary learning, so that they can enhance their vocabulary.